2011
DOI: 10.1177/1362361311413399
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the age at diagnosis of autism spectrum disorders in Nova Scotia, Canada

Abstract: While early diagnosis of autism spectrum disorders (ASD) is essential for ensuring timely access to early intervention services, there is limited existing literature investigating factors that delay this diagnosis. This population-based cohort study explored the age at which children in Nova Scotia, Canada, are diagnosed with ASDs and the factors associated with this age. Children diagnosed with an ASD between January 1992 and December 2005 were identified from a cohort of live births in the province between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 35 publications
3
30
1
3
Order By: Relevance
“…The presence of other developmental concerns or diagnoses may have masked or overshadowed an ASD diagnosis. 4,5,16 Indeed, in our cohort, we found that many children were diagnosed initially with developmental language disorders and motor difficulties, and almost half of the sample was diagnosed with ADHD features and behavior problems. 2.…”
Section: Discussionmentioning
confidence: 93%
“…The presence of other developmental concerns or diagnoses may have masked or overshadowed an ASD diagnosis. 4,5,16 Indeed, in our cohort, we found that many children were diagnosed initially with developmental language disorders and motor difficulties, and almost half of the sample was diagnosed with ADHD features and behavior problems. 2.…”
Section: Discussionmentioning
confidence: 93%
“…There have been several reviews and large-scale study reports of age at ASD diagnosis [810]. However, studies of age at ASD diagnosis have major problems.…”
Section: Introductionmentioning
confidence: 99%
“…Σε άιιε έξεπλα νη γνλείο αλαθέξνπλ όηη θαηά ηνπο πξώηνπο κήλεο ηα παηδία ηνπο αλαπηύζζνληαη θαλνληθά θαη από ηελ ειηθία 18-24 κελώλ άξρηζαλ λα παξαηεξνύλ ζπκπεξηθνξέο πνπ δεκηνπξγνύζαλ αλεζπρία αιιά αξρηθά ζεσξήζεθε ζαλ ραξαθηεξηζηηθό ηεο αλάπηπμήο ηνπο (Fernandez-Alcántara et al, 2016).Δίλαη γεγνλόο όηη γηα ηνπο γνλείο είλαη κηα πνιύπινθε δηαδηθαζία ε παξαηήξεζε θαη ε αλαγλώξηζε εθείλσλ ησλ ζηνηρείσλ πνπ παξαπέκπνπλ κε ζαθήλεηα ζηνλ απηηζκό λσξίηεξα ησλ 24 κελώλ εηδηθόηεξα αλ είλαη ην πξώην παηδί γηα λα γίλεη έγθαηξε παξέκβαζε (Frenette et al, 2011). Όζν ηα πξνεηδνπνηεηηθά ζεκάδηα απμάλνληαη, μεθηλά έλα «ηαμίδη» αλαδήηεζεο ησλ αηηηώλ αλάκεζα ζε δηάθνξεο εηδηθόηεηεο ηνπ θιάδνπ ηεο πγείαο κέρξη ηελ ηειηθή δηάγλσζε Γηαηαξαρή Απηηζηηθνύ Φάζκαηνο (Fernandez-Alcántara et al, 2016).…”
Section: ππώηα ζημάδια ηος αςηιζμούunclassified
“…Από ην θιάκα ηνπ ζξήλνπ έσο ηελ αθνζίσζε ζηε δνπιεηά ώζηε λα απνθεύγεη ην «πξόβιεκα», θάζε ηξόπνο εθδήισζεο αλαγλσξίδεηαη σο δηθαίσκα θαη γηα ην ιόγν απηόο είλαη ζεβαζηόο. Ζ έθθξαζε απηνύ ηνπ ζπλαηζζήκαηνο δίλεη ηε δπλαηόηεηα απειεπζέξσζεο ηεο ζπζζσξεπκέλεο έληαζεο ηνπ πόλνπ (AutismSpeaks, 2014;2011), (Νόηαο, 2005). …”
unclassified